2001
DOI: 10.1021/jo010217r
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Oxidation of Mustard-Model Sulfides Catalyzed by Iron and Manganese Tetraarylporphyrines. Oxygen Transfer To Sulfides versus H2O2 Dismutation and Catalyst Breakdown

Abstract: Fe(III)- and Mn(III)-meso-tetraarylporphyrin catalysis of H(2)O(2) oxidation of dibenzyl and phenyl-2-chloroethyl sulfides, 1, is investigated in ethanol with the aim of designing catalytic systems for mustard decontamination. The sulfide conversion, the sulfoxide and sulfone yields, the oxygen transfer from H(2)O(2) to the sulfide, and the catalyst stability depend markedly on the metal, on the substituents of its ligand, and on the presence or the absence of a cocatalyst, imidazole or ammonium acetate. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 44 publications
(77 reference statements)
0
25
0
Order By: Relevance
“…This complex is a highly potent and selective catalyst for the sulfoxidation of thioethers under mild conditions with H 2 O 2 as the terminal oxidant. This result is of practical significance, because sulfoxidation catalysts are important for both chemical synthesis12 and the decontamination of warfare agents 13. Moreover, H 2 O 2 is a desirable terminal oxidant because it is inexpensive and does not produce environmentally toxic byproducts.…”
Section: Methodsmentioning
confidence: 99%
“…This complex is a highly potent and selective catalyst for the sulfoxidation of thioethers under mild conditions with H 2 O 2 as the terminal oxidant. This result is of practical significance, because sulfoxidation catalysts are important for both chemical synthesis12 and the decontamination of warfare agents 13. Moreover, H 2 O 2 is a desirable terminal oxidant because it is inexpensive and does not produce environmentally toxic byproducts.…”
Section: Methodsmentioning
confidence: 99%
“…According to reasonable mechanisms, high‐valent iron–porphyrin intermediate PorFeV=O is a key intermediate in the catalytic transformation in the main step. However, as a side reaction, it can also promote the oxidative breakdown of the porphyrin ligand, which leads to a decrease in the amount of effective porphyrin catalyst sites during recycling. Therefore, the yield of the catalytic reaction gradually decreases each time when using the recycled catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the formation of the iron–oxo complex as the active species is a key step during the oxidation reaction catalyzed by iron–tetraarylporphyrins . The Ruasse group reported that iron–tetrakis(pentafluorophenyl)porphyrin (F20TPPFe) possessed a high catalytic efficiency as a catalyst for the H 2 O 2 ‐induced oxidation of mustard models among a number of iron–tetraarylporphyrins with different phenyl substituents in the ligands. Fluorinated phenyl substituents of the iron–porphyrin not only are beneficial to the conversion, but also can stabilize the porphyrin to prevent catalyst breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…Marques reported a new approach of mustard oxidation in a protic solvent with H 2 O 2 as an oxidant. 95 The results show that catalysis by Fe(III)-and Mn-(III)-tetraarylporphyrins (Scheme 14) can provide an interesting route to the transformation of mustard and related sulfides into sulfones. Differences in the behavior of Mn-and Fe-porphyrins for the efficiency in sulfide oxidation were also observed.…”
Section: Oxidation Of Sulfides To Sulfonesmentioning
confidence: 99%